Advokaters plikt i skatterättslig konflikt? - En studie om advokaters rapporteringsplikt av skatterättsliga arrangemang och regleringens förhållande till upprätthållandet av tystnadsplikten - Lax,Julia (2023)
Based on two conflicting obligations, the essay investigates how implementing the reporting obligation for tax arrangements (DAC6) and its limitation concerning lawyers relates to the duty of confidentiality. Additionally, the paper discusses how these aspects are influenced by the judgment of the Grand Chamber, C-694/20 Orde van Vlaamse Balies, which extended the EU legal professional privilege (LPP) by stating that the reporting obligation for intermediaries with national professional privileges may conflict with the respect for private and family life under Article 7 of the EU Charter. The paper establishes that the Swedish implementation of DAC6 resulted in vague and ambiguous provisions to avoid contradicting the directive’s purpose of enabling tax authorities to obtain information early and act against potential tax evasion. Furthermore, it results in various interpretations meaning that the answers regarding how the implementation relates to a lawyer’s duty of confidentiality may vary. Lawyers are subject to the legislation, and the requirements to be defined as an intermediary fall within the scope of “legal professional activates.” Consequently, lawyers must observe professional ethics, which includes a duty of loyalty to the client. The essay concludes that lawyers must assess to what extent they can disclose information about the tax arrangement without violating their duty in each case. Furthermore, the analysis determines that lawyers cannot provide any information about the arrangement following Section 33 b, chapter 16 of the Swedish Tax Procedure Act (SFL) to uphold their duty of confidentiality. According to Art. 8 ab (5) of the directive, the Member State must take necessary measures to ensure that the reporting obligation is promptly fulfilled when national regulations regarding professional privilege create such reporting obstacles. Consequently, Section 33 b, Chapter 22 of the SFL imposes an obligation to notify other intermediaries and, if applicable, the client about the reporting obligation. The Swedish Bar Association has interpreted this provision to oblige lawyers to express that there may be a reporting obligation generally, for example, on a website. However, based on preparatory work, the paper argues that the provision may be interpreted to mean that lawyers must notify other intermediaries in each individual case. The latter interpretation is argued to conflict with the extensive duty of individuality. In a Grand Chamber judgment on December 8, 2022, the court ruled that Article 8 ab (5) of DAC6 regarding the reporting obligation for intermediaries bound by national professional privilege violates the LPP encompassed in Article 7 of the EU Charter if the national implementation results in intermediaries having to notify without delay any other intermediary who is not his or her client of that intermediary’s reporting obligation. If section 33 b, Chapter 22 of the SFL implies that the intermediary is obliged to notify other intermediaries about the specific tax arrangement, information regarding the lawyer’s involvement, and the fact that the arrangement constitutes a reportable arrangement is disclosed, which undermines the confidentiality. Based on the Swedish duty of confidentiality and the extended LPP, the Swedish provision is argued to prevent lawyers from providing any information in accordance with Section 33 b, Chapter 16 of the SFL and from notifying other intermediaries about the reporting obligation in order to uphold the vital duty of confidentiality.
Keywords: Skatterätt; EU-rätt; DAC6; tystnadsplikt